Electrocatalytic glucose oxidation via hybrid nanomaterial catalyst of multi-wall TiO2 nanotubes supported Ni(OH)2 nanoparticles: Optimization of the loading level. (1st April 2015) - Gu, Yingying; Liu, Yicheng; Yang, Haihong; Li, Benqiang; An, Yarui
Graphical abstract: Highlights: Multi-wall TiO2 nanotube supported Ni(OH)2 nanoparticles, Ni(OH)2 /TNTs, was prepared and investigated as anode electro-catalysts for glucose oxidation. Ni(OH)2 -24.2%/TNTs obtains the best catalytic activity. Compared with Ni(OH)2, the current density of Ni(OH)2 -24.2%/TNTs increased 5.9 times in 0.1 M NaOH solution. Abstract: The novel hybrid nanomaterial catalyst of multi-wall TiO2 nanotube supported Ni(OH)2 nanoparticles (Ni(OH)2 /TNTs) was prepared through hydrothermal method and investigated as anode electro-catalysts for glucose oxidation. The nanostructure was characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscopy (TEM), thermogravimetry-differential thermal analysis (TGA) and nitrogen adsorption-desorption (BET-BJH). The electrochemical performance was measured by a range of electrochemical measurements. Compared with Ni(OH)2, the current density of Ni(OH)2 /TNTs modified GC electrode increased 5.9 times in 0.1 M NaOH solution. The results indicated that the synthesized nanoparticles exhibited good electro-catalytic activity and stability for glucose oxidation. Meanwhile, the hybrid nanomaterial of Ni(OH)2 /TNTs may be a potential candidate catalyst for direct glucose fuel cell.